TAKOTSUBO SYNDROME – CURRENT KNOWLEDGE AND CLINICAL CHALLENGES - Barbara Starosta; Bartosz Brzychcy; Zuzanna Gajda; Monika Pelczar; Karolina Brzychcy; Karolina Paks; Ewa Jench; Natalia Musialik; Maciej Magiera; Filip Kochański (International Journal of Innovative Technologies in Social Science, 2025)
"Broken heart syndrome" is one of several terms used to describe Takotsubo syndrome. This name refers to the fact that severe emotional or physical stress is considered to be a triggering factor for the disease. Takotsubo syndrome is an acute cardiac condition characterized by reversible ventricular dysfunction and various cardiac wall-motion abnormalities. It presents with a symptom profile that closely resembles acute coronary syndrome. Therefore, it is usually underdiagnosed, especially in patients who have co-existing coronary artery disease. Despite its transient nature, the condition may be associated with various life-threatening complications including arrhythmias, acute heart failure, cardiogenic shock, ventricular thrombus and risk for cerebrovascular events. Purpose: The aim of this review is to present the current state of knowledge about Takotsubo syndrome and to highlight aspects that require further investigation and systematization. Materials and Methods: A literature review was conducted from the PubMed database, covering studies from 2015-2025. Key phrases such as “Takotsubo Syndrome”, “Broken Heart Syndrome”, “Stress Cardiomyopathy” were used. Selected papers were analyzed and evaluated for conclusions. Conclusions: Takotsubo syndrome remains incompletely understood, with significant gaps in its diagnostic criteria, therapeutic management, and strategies for preventing recurrence. Further research, including large-scale clinical trials and comprehensive meta-analyses, is essential to establish evidence-based guidelines and improve patient outcomes.